KEMAMPUAN PENALARAN MATEMATIKA SISWA MELALUI MODEL PEMBELAJARAN CORE AND PAIRS CHECK (CPC) PADA MATERI STATISTIKA SISWA KELAS XI MA MA’ARIF NU JENGGAWAH - Nana Maulidah Agustin (Universitas Islam Malang, 2019)
The purpose of this study was to determine the differences in mathematical reasoning abilities of students in class XI on statistical material through the CPC learning model and conventional models and describe the results of analysis of mathematical reasoning abilities of class XI students through CPC learning models and conventional models on statistical material. This study was a mixed method with a sequential explanatory design. The sample from this study was XI IPA 1 and XI IPA 2 MA Ma'arif NU Jenggawah. While the subject of qualitative research was 6 students from the experimental class and the control class students selected based on high, medium, and low reasoning abilities. Data collection is done by test, observation, field notes and interviews. The analysis technique uses prerequisite tests, namely t-test and qualitative descriptive. Based on the results of quantitative research, using SPSS 16 software obtained Sig = 0,000 <0,025 so that it was rejected, meaning that there was a significant difference between mathematical reasoning abilities of the experimental class students using CPC models and control classes using conventional models in statistical material. While the qualitative analysis shows that based on the results of interviews on experimental class subjects, an average of 88% of students have fulfilled five reasoning indicators while in the control class only 56% of students meet the five indicators of mathematical reasoning.